Profile of Knowledge on Stroke among Paramedics at Jatinangor and Tanjungsari Public Health Centers - Rangga Kusuma Wardhana; Andi Basuki; Suryosutanto Suryosutanto (Faculty of Medicine Universitas Padjadjaran, 2016)
Background: A knowledge of stroke is important for paramedics, to minimize delays and increase the numbers of potentially treatable patients. Paramedics are health workers who devote themselves in the field of health, have knowledge and/or skills through education in the health field that requires authority in running health services. The aim of this study was to measure the level of knowledge of paramedics about stroke in Jatinangor and Tanjungsari Public Health Center.Methods: A cross–sectional descriptive study was conducted from August to October 2013. An 11-item questionnaire has been established and were submitted to 43 paramedics at Jatinangor and Tanjungsari Public Health Center.The determination of level of knowledge was based on the T–score of each respondent compared with the mean T–score of the subject population.Result: The most respondents were female. Midwifery had the highest frequency of respondents. Largely, the source of information about stroke derived from education.The mean of T-score was 50. There were 28 respondents had a good level of knowledge about stroke and 15 respondents had a poor level of knowledge about stroke.Conclusions: Most paramedics have a good level of knowledge of stroke. [AMJ.2016;3(3):355–8]DOI: 10.15850/amj.v3n3.879